Mild Hypothermia via External Cooling Improves Lung Function and Alleviates Pulmonary Inflammatory Response and Damage in Two-Hit Rabbit Model of Acute Lung Injury. Issue 7 (14th July 2022) - Akyol, Onat; Demirgan, Serdar; Şengelen, Aslıhan; Güneyli, Hasan Cem; Oran, Duygu Sultan; Yıldırım, Funda; Haktanır, Damla; Sevdi, Mehmet Salih; Erkalp, Kerem; Selcan, Ayşin
Abstract: Objectives: Targeted temperature management (TTM) with therapeutic hypothermia (TH) has an organ-protective effect by mainly reducing inflammatory response. Here, our objective was to determine, for the first time, whether mild TH with external cooling, a simple and inexpensive method, could be safe or even beneficial in two-hit rabbit model of acute lung injury/acute respiratory distress syndrome (ALI/ARDS). Methods: Twenty-two New Zealand rabbits (6-month-old) were randomly divided into healthy control (HC) with conventional ventilation, but without injury, model group (ALI), and hypothermia group with external cooling (ALI-HT). After induction of ALI/ARDS through mild lung-lavages followed by non-protective ventilation, mild hypothermia was started in ALI-HT group (body temperature of 33–34 °C). All rabbits were conventionally ventilated for an additional 6-h by recording respiratory parameters. Finally, lung histopathology and inflammatory response were evaluated. Results: Hypothermia was associated with higher oxygen saturation, resulting in partial improvement in the P/F ratio (PaO2 /FiO2 ), oxygenation index, mean airway pressure, and PaCO2, but did not affect lactate levels. The ALI-HT group had lower histopathological injury scores (hyperemia, edema, emphysema, atelectasis, and PMN infiltration). Further, tumor necrosis factor-alpha (TNF-α), interleukin (IL)-6 and −8 levels in lung tissue and serum samples markedly reduced due to hypothermia. Conclusion: Mild TH with external cooling reduced lung inflammation and damage, whereas it resulted in partial improvement in gas exchanges. Our findings highlight that body temperature control may be a potentially supportive therapeutic option for regulating cytokine production and respiratory parameters in ALI/ARDS.